Implementasi Penyelenggaraan Reklame di Kabupaten Badung - I Made Purnayasa; Ida Ayu Putu Widiati; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2024)
In its implementation, billboards often use public facilities that should not function as a place or means of promotion. This results in irregularities in the licensing field with the Government such as in Badung Regency. Based on this, how is the implementation of billboard installation in Badung Regency? And how is the control of the implementation of billboard installation in Badung Regency? Research writing uses empirical legal methods. Based on Badung Regent Regulation Number 80 of 2014, the installation of billboards must pay attention to aesthetics, ethics and beauty, where in Badung Regency there is still a lot of overlap in the practice of installation places. In this case, the Badung Regency Government has a Master Plan (location of billboard distribution) to issue permits for the implementation of billboards that are not in accordance with the rules, by making repressive and preventive efforts such as demolition and socialization of the rules for billboards and processing billboard permits.